The invention of Germany in the nineteenth century: Kleist and Fichte as propagators - Horn, Peter (Acta Academica: Critical views on society, culture and politics, 2010)
During the French Revolution and the ensuing wars both France and Germany developed an entirely new concept of the nation. In Germany Heinrich von Kleist and Johann Gottlieb Fichte, among others, were imagining “Germany” in a territory which had no such national unity. Similar processes take place wherever feudal or traditional societies are reinventing themselves as nation states. Nation is the imaginary construct of a bounded community (state) whose inner and outer boundaries simultaneously include and exclude. While the concept of an “imagined” community addresses some of the aspects of nationalism, this “imagination” does not come about by itself, but has to be “invented” and the citizens of this community have to be indoctrinated by “education” and propaganda.